Implementation of the Merdeka Curriculum Using Citizen Science Project Weather-it to Improve Critical Thinking Skills of Junior High School Students - St E Sururiyatul Muaziyah; Topik Hidayat; Siti Sriyati; Lia Lutianasari (Postgraduate, University of Mataram, 2023)
The Merdeka curriculum requires teachers and educational units to provide project activities in student learning. The project activities aim to improve students' skills, one of which is critical thinking. This study aims to see the feasibility of the citizen science project, Weather-it, as part of project activities in the Merdeka curriculum to improve students' critical thinking skills. This study uses the Pre-experimental method with the One-Group Pretest-Posttest Design. A total of 42 grade 7 students at a junior high school in Bandung took part in the citizen science project, Weather-it. The validated pre-test and post-test questions were made and used to analyze the improvement of students' critical thinking skills. This increase can be seen from changes in the average pre-test and post-test scores and by calculating the N-Gain score. The results showed an increase in the average value of students' critical thinking, from 48.75 (pre-test) to 70.41 (post-test). The N-Gain score states the effectiveness of the citizen science project, Weather-it, where 57.1% of students are in the medium category, 28.6% in the high category and 14.3% in the low category. Likewise, the results reflect how the citizen science project, Weather-it, can be implemented as part of implementing the Merdeka curriculum